Successful treatment of refractory chronic bullous disease of childhood with rituximab - Debdeep Mitra; Anuj Bhatnagar; Gautam K Singh; Sunmeet Sandhu (Wolters Kluwer Medknow Publications, 2022)
Chronic bullous disease of childhood is a rare subepidermal bullous disease with a hallmark of linear IgA deposition along basement membrane zone seen on direct immunofluorescence. We report a case of a 2-year-old male child, who had recurrent and multiple bullous eruptions over body and he was not responding to conventional therapy. He had earlier developed a drug reaction to dapsone which is considered the drug of choice for this condition. We report successful management of this case with injection rituximab which is a chimeric monoclonal antibody against CD20, which is primarily found on the surface of B cells.